Characterisation of Bifidobacterium induced from prebiotic (Galactooligosaccharide) supplemented pigs - Stanley, James (2022)
Pork is the second most consumed meat worldwide and due to its increasing global demand, there is a requirement for the commercial pig farming industry to maintain efficient production while maintaining good animal welfare standards. Since the use of antibiotics as growth promoters was banned in the EU, the use of dietary fibres as prebiotics for growth promotion in livestock is a rapidly expanding area of scientific research. As such, bacteria that are significantly affected following the addition of prebiotics to animal feed are of great interest to understand the microbe-host relationship. Bifidobacteria inhabit the mammalian gastrointestinal tract and confer several host health benefits such as increased luminal short-chain fatty acid (SCFA) concentrations, lower pathogenic colonisation in the gut and reduced intestinal inflammation. Prebiotic galacto-oligosaccharides (GOS) have been shown to enrich Bifidobacterium populations in the hindgut, which has been correlated with increased acetate, butyrate and propionate production. Such SCFA are also suggested to improve fat and protein retention. This study aims to sequence Bifidobacterium spp. isolated from pigs fed a GOS supplemented diet and identify coding regions responsible for GOS metabolism and SCFA synthesis. Bacteria isolated from pig caecal and colonic samples were sequenced using the Illumina MiSeq sequencing platform. The complete genome sequences of Bifidobacterium animalis subsp. lactis, Bifidobacterium pseudolongum and Lactobacillus reuteri are reported. The assembled circular genomes were 1.96 (B. animalis subsp. lactis), 1.94 (L. reuteri) and 1.97 (B. pseudolongum) Mb and comprised of 1542, 1772-1774 and 1570-1572 protein coding genes, respectively. B. animalis subsp. lactis possessed genes for both the LacS/LacZ and LacEF/LacG pathways to fully metabolise GOS, whereas L. reuteri and B. pseudolongum possessed only the LacS/LacLM and LacS/LacZ, respectively. Furthermore, both Bifidobacteria possess ackA and tesB, genes responsible for producing proteins involved in acetate and butyrate synthesis, whereas L. reuteri only possessed ackA.